The evolutionary diversification of the Salmonella artAB toxin locus - Ojiakor, Adaobi; Gibbs, Rachel N.; Chen, Zhe; Gao, Xiang; Fowler, Casey C. (Frontiers in Microbiology, 2022)
Salmonella enterica is a diverse species of bacterial pathogens comprised of >2500 serovars with variable host ranges and virulence properties. Accumulating evidence indicates that two AB5-type toxins, typhoid toxin and ArtAB toxin, contribute to the more severe virulence properties of the Salmonella strains that encode them. It was recently discovered that there are two distinct types of artAB-like genetic elements in Salmonella: those that encode ArtAB toxins (artAB elements) and those in which the artA gene is degraded and the ArtB homolog, dubbed PltC, serves as an alternative delivery subunit for typhoid toxin (pltC elements). Here, we take a multifaceted approach to explore the evolutionary diversification of artAB-like genetic elements in Salmonella. We identify 7 subtypes of ArtAB toxins and 4 different PltC sequence groups that are distributed throughout the Salmonella genus. Both artAB and pltC are encoded within numerous diverse prophages, indicating a central role for phages in their evolutionary diversification. Genetic and structural analyses revealed features that distinguish pltC elements from artAB and identified evolutionary adaptations that enable PltC to efficiently engage typhoid toxin A subunits. For both pltC and artAB, we find that the sequences of the B subunits are especially variable, particularly amongst amino acids residues that fine tune the chemical environment of their glycan binding pockets. This study provides a framework to delineate the remarkably complex collection of Salmonella artAB/pltC-like genetic elements and provides a window into the mechanisms of evolution for AB5-type toxins.